Development of Interactive Mathematics E-Modules Based on Local Issues with a Personalized Approach to Facilitate Junior High School Students' Computational Thinking Skills - Ratau, Asria; Bugis, Halima; Wagola, Wa Nurmin; Hukom, Julham (MATHEMA: JURNAL PENDIDIKAN MATEMATIKA, 2025)
Computational thinking is a method or problem-solving technique that uses concepts from computer science, some characteristics of computational thinking are abstraction, problem decomposition, algorithmic thinking, and generalization. One of the efforts that can generally be done to facilitate students' computational thinking is to facilitate teaching materials (e-modules). Several previous studies have conducted various developments of mathematics e-modules, but there are several weaknesses including the materials and instruments are less related to the context or local issues in the student's environment, the materials and instruments are not oriented to the computational thinking aspect, the e-modules developed pay less attention to the interactivity aspect, so that students do not get optimal feedback from teachers and make it difficult for teachers to control students' abilities, and the e-modules developed do not facilitate students' diverse initial abilities, so a personalized approach is needed in developing e-modules. Therefore, this study aims to produce interactive mathematics e-modules based on local issues or local issues with a personalized approach to facilitate junior high school students' computational thinking abilities. This research is a research & development (R&D) using the Borg and Gall development model. The results of our study indicate that interactive mathematics e-modules based on local issues or local issues with a personalized approach are declared feasible, practical, and effective in facilitating junior high school students' computational thinking. These findings can provide significant contributions in the field of education, especially in teaching mathematics that is more contextual and adaptive to students' needs.